How Eye Movements Stabilize Posture in Patients With Bilateral Vestibular Hypofunction - Lacour, Michel; Dosso, Nadine Yavo; Heuschen, Sylvie; Thiry, Alain; Van Nechel, Christian; Toupet, Michel (Frontiers in Neurology, 2018)
Chronic patients with bilateral vestibular hypofunction (BVH) complain of oscillopsia and great instability particularly when vision is excluded and on irregular surfaces. The real nature of the visual input substituting to the missing vestibular afferents and improving posture control remains however under debate. Is retinal slip involved? Do eye movements play a substantial role? The present study tends to answer this question in BVH patients by investigated their posture stability during quiet standing in four different visual conditions: total darkness, fixation of a stable space-fixed target, and pursuit of a visual target under goggles delivering visual input rate at flicker frequency inducing either slow eye movements (4.5 Hz) or saccades (1.2 Hz). Twenty one chronic BVH patients attested by both the caloric and head impulse test were examined by means of static posturography. The posturography data were analyzed using non-linear computation of the center of foot pressure (CoP) by means of the wavelet transform (Power Spectral Density in the visual frequency part, Postural Instability Index) and the fractional Brownian-motion analysis (stabilogram-diffusion analysis, Hausdorff fractal dimension). Results showed that posture stability was significantly deteriorated in darkness in the BVH patients compared to normative data recorded in age-matched healthy controls. Strong improvement of BVH patients’ posture stability was observed during fixation of a visual target, pursuit with slow eye movements, and saccades. It is concluded that BVH patients improve their posture stability by 1) using extraocular signals from eye movements (efference copy, muscle re-afferences), and 2) shifting to a more automatic mode of posture control when they are in dual-task conditions associating the postural task and a concomitant visuo- motor task. Key Words: Bilateral Vestibular Hypofunction Patients – static posturography – darkness – visual fixation – slow eye movements - saccades